Do Fossil-Fuel Price Distortions Impact the Low-Carbon Transition in China’s Energy Intensive Industries? - Wang, Xiaolei; Liang, Shuang; Wang, Hui; Huang, Shaohua; Liao, Binbin (Frontiers in Energy Research, 2022)
Energy intensive industries (EIIs) in China are predominantly reliant on fossil fuels. Consequently, such high fossil fuel dependency has amplified carbon emission levels and blocked the low-carbon transition. It is inappropriate to discuss the solution of the dependency before investigating fossil-fuel price distortion and its impact on the industrial energy consumption. Therefore, this paper built a dynamic trans-log cost function model based on provincial panel data of China’s Ells between 2004 and 2016, to investigate inter-fuel substitution effects caused by own price elasticities and cross price elasticities, and analyzed the impact of fossil-fuel price distortions on low-carbon transition. The level of price distortions in coal, gasoline and diesel was evaluated, based on which the CO2 mitigation potentials in China’s EIIs were estimated. Results show that: 1) in each EII sector, the own price elasticities of all fuels were negative while the cross price elasticities among coal, oil and electricity were positive, suggesting substitution effect exists; 2) the average level of price distortions in coal, gasoline and diesel is 7.48, 11.1 and 32.19%, respectively, which means the prices of coal tend to be more market- oriented than the other two fuels; 3) removing coal price distortions can potentially reduce CO2 emissions in China’s EIIs by 905.78 million tons, while the effects of removing oil price distortions were uncertain, unless the substitution of coal for oil was restrained. Therefore, there is still much room for improvement in China’s fossil-fuel market reform. Possible policies are required to improve the production in EIIs and the low-carbon transition by adopting cleaner energy resources to substitute fossil-fuels.